Comparative Evaluation of Deciduous and Permanent Coronal Caries Using Polarizing Light Microscopy and Scanning Electron Microscopy - Nithya Annie Thomas; Sreena T.; Charisma Thimmaiah; Pinky Varghese; Nimmy Sabu; Pretty Prince P.; Athira Kattachirakunnel Sasi (The Scientific World Journal)
Conclusion: Our findings suggest that caries destruction is more prevalent in deciduous teeth, and reactive response is more effective in permanent teeth affected by caries. These findings reflect the structural durability of the mineralized tissues and prompt reactive response of the dentin pulp complex of permanent teeth compared to deciduous teeth. Our research highlights the importance of identifying and treating decay in primary teeth at an early stage.